2021
DOI: 10.21203/rs.3.rs-909431/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heart rate variability changes in mild-symptomatic, physically fit male in 4-6 weeks from the end of SARS-Cov-2 infection

Abstract: SARS-Cov-2 infection, due to inflammation processes, can affect autonomic nervous system and heart rate variability (HRV) even after disease. Previous studies showed significant changes in HRV parameters in severe (including fatal) infection of SARS-Cov-2. However, HRV analysis for the asymptomatic or mild-symptomatic Covid-19 patients have not been reported. In this study, we suggested that there is an influence of a SARS-Cov-2 infection on the HRV in such patients after weeks form disease.Sixty-five ECG Holt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The evaluation of the ANS can be obtained from a combination of microneurography and continuous measurements of catecholamines; however, such measurements are difficult to obtain. On the other hand, it has been shown that autonomic activity can be evaluated through the specific analysis of heart rate variability (HRV) [2,12]. However, the studies on COVID-19 are not conclusive and present contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the ANS can be obtained from a combination of microneurography and continuous measurements of catecholamines; however, such measurements are difficult to obtain. On the other hand, it has been shown that autonomic activity can be evaluated through the specific analysis of heart rate variability (HRV) [2,12]. However, the studies on COVID-19 are not conclusive and present contradictory results.…”
Section: Introductionmentioning
confidence: 99%